Pembuatan Alat Pelipat Baju Otomatis Berbasis Arduino Uno Untuk UMKM Laundry - Umurani, Khairul; Rahmatullah, Rahmatullah; Muharnif, M.; Asfiati, Sri; Sandi, Didik Mei (Rekayasa Material, Manufaktur dan Energi, 2025)
Laundry workers are required to be able to fold quite a lot of clothes in a fairly short time and neatly. Based on this, an innovation is needed in terms of folding clothes that can help household chores and the UMKM scale laundry industry in terms of folding clothes. The main aim of the research is to create an Arduino-based automatic clothes folding device. Arduino Uno is a microcontroller that is often used in making prototypes of electronic circuits which are useful for making things easier for users. Making an Arduino-based module requires a circuit schematic which is useful for making things easier when making tools. Electronic circuit schematics are needed as a guide in making electronic circuits. The electronic circuit schematic should be designed or drafted first before carrying out the process of making the electronic circuit. Testing of this servo motor is carried out by starting the rotation of the servo motor from an angle of 0⁰ to a rotation of 180⁰. The test results can be concluded that the three servo motors used are in good condition. Having an automatic clothes folding tool can help with daily housework and help laundry entrepreneurs in folding clothes neatly, saving time and energy. The time required to fold a short-sleeved t-shirt is 3.56 seconds and a short-sleeved shirt is 3.66 seconds